Analisis Strategi Penerapan Sistem Manajemen Keamanan Pangan HACCP (Hazard Analysis and Critical Control Points) di PT. Sierad Produce Tbk. Parung - Arfiansyah Sutrisno; Abdul Basith; Nur Hadi Wijaya (IPB University, 2013)
Quality and safety food products problem was usually after thought in the food industry development issues, accordance with the consumer’s desirability that understand the importance of product quality and food safety. Hazard Analysis and Critical Control Points (HACCP) certification is one way for company to implementing food safety. Sierad Produce Corp. at this moment has obtained HACCP certificate to produce chicken carcasses.But the implementation need to be controlled, as the case of foodborne illness and foodborne disease can occur easily if not properly controlled. The main objective of this research is to develop the best strategy to implement HACCP and to maintain the food safety quality system at Sierad Produce Corp. The information and data that has been collected within this research were covering both the primary and secondary data based on the date of September 2012 to December 2012. The methods used in this research are descriptive analysis, Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), Internal External (IE), Strength Weakness Opportunity Threat (SWOT) and Analysis Hierarchy Process (AHP). Based on this research, the best strategy for implementing HACCP and sustain the system on Sierad Produce are Critical Control Points (CCP) evaluation and improvement of production room.Keywords: AHP analysis, chicken slaughterhouse, HACCP, sierad produce, strategy